Dynamical Symmetry Breaking in RN Quantum Gravity - A. T. Kotvytskiy; D. V. Kruchkov (Acta Polytechnica, 2011)
We show that in the RN gravitation model, there is no dynamical symmetry breaking effect in the formalism of the Schwinger-Dyson equation (in flat background space-time). A general formula for the second variation of the gravitational action is obtained from the quantum corrections hμν (in arbitrary background metrics).